Association of type 1 diabetes mellitus (DM1) with polymorphous alleles of HLA-DR and DQ genes in two Russian populations of Moscow and Vologda regions - Tamara Leonidovna Kuraeva (Endocrinology Research Centre, 2009)
Aim. To consider association of type 1 diabetes mellitus (DM1) with polymorphous alleles of HLA-DRB1 HLA-DQB1, and DQA1 genes in two Russian populations of Moscow (MP) and Vologda (VP) regions. Materials and methods. Identification of alleles of HLA-DRB1 HLA-DQB1, and DQA1 genes in 138 patients with type 1 diabetes and a random sample of 242 subjects from the local population (residents in at least three successive generations) of the Vologda region, 204 patients and a random sample of 300 subjects from the city of Moscow and Moscow region. Results. MP and VP exhibited identical predisposing alleles. The occurrence of DRB1*4 (RR=5.96 and 3.93 in MP and VP respectively), DRB1*17 (RR=4.33 and 4.23), DQA1*0301 (RR=5.70 and 3.66), DQB1*0201, (RR=2.06 and 1.77), DQB1* 0302 (RR=7.10 and 3.95), DQB1* 0304 (RR=8.94 and 19.98) alleles was significantly higher in DM1 patients. The following protective alleles were identified in MP and VP respectively: DRB1*7 (RR=0.37 and 0.18), DRB1*11 (RR=0.12 and 0.21), DRB1*13 (RR=0.09 and 0.26), DRB1*15 (RR=0.23 and 0.04), DQA1*0102 (RR=0.29 and 0.23), DQA1*0103 (RR=0.13 and 0.23), DQA1*0201 (RR=0.37 and 0.17), DQb1*0301 (RR=0.16 and 0.24), and DQB1*0602/8 (RR=0.10 and 0.13). Conclusion. ?New? associations unknown in other populations (e.g. DQB1*0304) were revealed, besides the majority of classical predisposing and protective alleles characteristic of European populations. DQB1*0304 proved the strongest predisposing allele in MP and especially in VP. These data suggest different contribution of predisposing alleles to the development of DM1 in individual populations.